1993
DOI: 10.1212/wnl.43.11.2303
|View full text |Cite
|
Sign up to set email alerts
|

Posthypoxic treatment with felbamate is neuroprotective in a rat model of hypoxia‐ischemia

Abstract: Felbamate, a novel dicarbamate anticonvulsant that blocks the glycine site of the N-methyl-D-aspartate receptor and protects the hippocampal slice from hypoxic damage, shows remarkably low toxicity in animals and in humans. Since most treatment of human cerebral ischemia will have to be delivered after the insult, we investigated the neuroprotective potency of post hoc felbamate in rat pups with bilateral carotid ligations exposed to an atmosphere of 6.5% O2 for 1 hour. Brain temperature was unaffected by surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The number of necrotic neurons in the dentate gyrus was reduced by 77% over the controls. Felbamate was also neuroprotective when it was administered after ischemia [54,56]. These data suggest that, in this animal model, felbamate is effective in reducing cerebral infarction and extremely effective in preventing delayed neuronal necrosis.…”
Section: Global Ischemic Brain Injurymentioning
confidence: 54%
See 1 more Smart Citation
“…The number of necrotic neurons in the dentate gyrus was reduced by 77% over the controls. Felbamate was also neuroprotective when it was administered after ischemia [54,56]. These data suggest that, in this animal model, felbamate is effective in reducing cerebral infarction and extremely effective in preventing delayed neuronal necrosis.…”
Section: Global Ischemic Brain Injurymentioning
confidence: 54%
“…Wasterlain et al [54,55] tested the neuroprotective effects of felbamate in a model of incomplete cerebral ischemia and hypoxia in 7-day-old rats. Felbamate treatment before ischemia (300 mg/kg) reduced the surface of infarcted cortex by 42-49% compared to controls.…”
Section: Global Ischemic Brain Injurymentioning
confidence: 99%
“…Previous studies 22,30 have shown that granule cells of the dentate gyrus that undergo apoptosis 31,32 and in caspase-deficient mice. 33 Further investigation of excitotoxicity in cerebral ischemia may lead to a better understanding of modes of cell death such as apoptosis and necrosis and to more effective stroke treatments in the future.…”
Section: Discussionmentioning
confidence: 97%
“…20 A model of cerebral hypoxia-ischemia has been developed in the neonatal rat that reliably produces infarction primarily involving the cortex in the territory of the middle cerebral artery and selective neuronal death of the inner granule cell layers of the dentate gyrus. [21][22][23] The purpose of this study was to determine whether this model of ischemic damage in the cerebral cortex and inner granule cell layers of the dentate gyrus demonstrates evidence of apoptosis.…”
Section: See Editorial Comment Page 2629mentioning
confidence: 99%
“…Unfortunately, most of these NMDA antagonists are only available as an intravenous formulation. Dextromethor phan, felbamate and remacemide are orally available NMDA antagonists [6,7], Another method to impede these channels is to inhibit presynaptic glutamate release by blocking sodium-conducting channels [8]. Sodium channel blockers, such as fos-phenytoin and BW1003C87, are effective in animal stroke models [9], Riluzole, an orally available modulator of glutamate re lease with a good safety profile, reduced mortality in amyotrophic lateral sclerosis [10].…”
mentioning
confidence: 99%